تطبيق نظرية الموظف الفعلي في الظروف الاستثنائية - داود، حلا عزيز داود (الجمعية العلمية للدراسات التربوية المستدامة, 2024)
تتناول نظرية الموظف الفعلي (نظرية الموظف الواقعي) دور الموظفين الفعليين في المؤسسات العامة وتأثيرهم خلال الظروف الاستثنائية. تنبع هذه النظرية من الحاجة إلى الحفاظ على استمرارية العمل الحكومي والإداري في الأوقات الحرجة، مثل الأزمات السياسية أو الكوارث الطبيعية أو الحروب. في مثل هذه الحالات، قد يصبح من الصعب الالتزام بالمتطلبات القانونية والإدارية التقليدية، مما يستدعي وجود إطار قانوني وتنظيمي يسمح للموظفين الفعليين بالتصرف واتخاذ القرارات اللازمة لضمان استمرارية الخدمات العامة. نظرية الموظف الفعلي تعنى بالاعتراف بالقرارات والإجراءات التي يتخذها الأفراد الذين قد لا يكون لديهم تفويض قانوني أو إداري كامل، ولكنهم يتصرفون بحسن نية وفي إطار محاولة الحفاظ على النظام العام وتسيير الأعمال الحكومية. تركز هذه النظرية على الشرعية الوظيفية للأفعال بدلا من الشرعية القانونية البحتة يتعين على هؤلاء الموظفين اتخاذ قرارات سريعة وفعالة لضمان تلبية الاحتياجات العامة الطارئة، وذلك غالبا في ظل غياب الموظفين المعتمدين أو عدم القدرة على الاتصال بهم. في الظروف الاستثنائية، تصبح السرعة والكفاءة في اتخاذ القرارات الإدارية أمرا حاسما. قد تؤدي البيروقراطية التقليدية والالتزام الصارم بالإجراءات القانونية إلى تأخير لا يمكن تحمله في أوقات الأزمات. لذلك، توفر نظرية الموظف الفعلي مرونة قانونية تتيح للموظفين التصرف بشكل سريع وفعال، مما يساهم في استقرار المجتمع وحماية المصلحة العامة. تقدم نظرية الموظف الفعلي إطارا حيويا ومرنا يتيح التعامل الفعال مع الظروف الاستثنائية، مما يضمن استمرار تقديم الخدمات العامة وحماية المصلحة العامة في الأوقات الحرجة. ومع ذلك، يجب موازنة هذه المرونة بآليات رقابية وضوابط صارمة لمنع إساءة استخدام السلطة وضمان العودة السريعة إلى الأطر القانونية التقليدية فور انتهاء الأزمات. The theory of the actual employee (the de facto officer theory) addresses the role of actual employees in public institutions and their impact during exceptional circumstances. This theory stems from the need to maintain the continuity of governmental and administrative work during critical times, such as political crises, natural disasters, or wars. In such cases, adhering to traditional legal and administrative requirements may become challenging, necessitating a legal and regulatory framework that allows actual employees to act and make necessary decisions to ensure the continuity of public services. The theory of the actual employee recognizes the decisions and actions taken by individuals who may not have full legal or administrative authorization but act in good faith and within the scope of maintaining public order and managing governmental affairs. This theory focuses on the functional legitimacy of actions rather than strict legal legitimacy. These employees must make quick and effective decisions to meet urgent public needs, often in the absence of authorized personnel or the inability to contact them. In exceptional circumstances, speed and efficiency in administrative decision-making become crucial. Traditional bureaucracy and strict adherence to legal procedures may lead to intolerable delays during crises. Therefore, the theory of the actual employee provides legal flexibility that allows employees to act swiftly and effectively, contributing to societal stability and the protection of public interest. The theory of the actual employee offers a vital and flexible framework for effectively handling exceptional circumstances, ensuring the continuous provision of public services and protecting the public interest during critical times. However, this flexibility must be balanced with oversight mechanisms and strict controls to prevent abuse of power and ensure a swift return to traditional legal frameworks once the crises have ended.
Keywords: العمل الحكومي -- اتخاذ القرارات -- الإجراءات القانونية -- الخدمات العامة